Efecto de bioestimulantes en el crecimiento de plántulas de tara (Caesalpinia spinosa) en vivero de la Universidad Nacional de Loja - Flores Jirón, Jenny Olinda (2024)
Nowadays the demand in the industry for the cultivation of Tara (Caesalpinia spinosa) has increased, because of its tannin content of its fruit; besides, the tree is characterized for being multipurpose, it is used for timber, medicinal uses, soil conservation, and its leaves are used for cattle feeding. Little is known about the propagation of this species in the province of Loja, for this reason it is important to provide information that will help in the production of quality seedlings with adaptive ability and survival in the field. In this research, the effect of the application of biostimulants on the growth and physiological behavior of Tara seedlings in nursery was evaluated. A completely randomized design (CRD) was used, with nine treatments (biostimulants + control) and four repetitions. An ANOVA analysis of variance and Tukey's tests of 95% confidence were carried out for all variables. The biostimulant with favorable results in plant height, number of leaves, stem diameter and leaf dry biomass was the product Agromin with 13.12 cm, 13.1 cm, 0.22 cm and 0.76 %, respectively. For root length it was found that Alga active reached 13.72 cm, while for root dry biomass Tricho-plus® outperformed the other treatments with 0.87 %. The biostimulants based on (Ascophylum nodosum) showed the best results in the propagation of Cesalpinia spinosa in the nursery stage. The use of the biostimulant Agromin in foliar and soil fertilization is recommended to improve the quality and development of the seedlings.